Exploring the Dynamics of Interpersonal Communication in Inmate Rehabilitation Programs at LAPAS KELAS II A Kendari - Jamin, Siti Nur Kholifah; Syamsu, Khairunnisa (Institut Agama Islam Negeri Kendari, 2024)
This study aims to determine the interpersonal communication of LAPAS employees in fostering assisted citizens in class II A Kendari Penitentiary. The research method used is descriptive qualitative, data collection in this study uses qualitative methods by observation, interviews, documentation and data analysis. This research involved 9 resource persons, namely 5 LAPAS employees and 4 assisted residents. The results showed that interpersonal communication of LAPAS employees in fostering fostered citizens involved several main aspects, namely. Openness from LAPAS employees is listening to complaints, opinions or ideas, providing good service and clearly providing information about the rules. Empathy of LAPAS employees understands and cares.The supportive attitude of LAPAS employees is in the form of moral support, material support, and assimilation support. The positive attitude of LAPAS employees is to be a good role model, control emotions, direct fostered residents in a good direction. The equality aspect of LAPAS employees is to be fair without any discrimination. Supporting factors for coaching are stakeholders, moral support from employees, premium wages for fostered residents, and security employees. The inhibiting factors of coaching are low awareness of fostered residents, low employee competence, and limited budget.Keywords: Coaching, Fostered Citizen, Interpersonal Communication.